Effect of high- and low-side blocking on short-circuit characteristics of SiC MOSFET. (August 2021) - Bai, Kun; Feng, Shiwei; Zheng, Xiang; He, Xin; Pan, Shijie; Li, Xuan
Abstract: Silicon carbide (SiC) metal oxide semiconductor field-effect transistors (MOSFETs) are susceptible to unexpected short-circuit (SC) impacts in high-voltage inverters operating in complex applications. This paper presents a research on the effect of high-side blocking and classical low-side blocking on short circuit characteristics. Simulation of the steady-state electric field, which equivalent to the states after LSB and HSB, was performed. The obvious electric field concentration appears in the source-drain pn junction of the DUT after the LSB, and is much larger in value than that appearing in the DUT after the HSB. DUTs, which failed, were decapsulated from the side of the drain to allow for an emission microscope (EMMI) investigation. In response to the results of the EMMI investigation, it was discussed that the occurrence of source leakage was caused by electric field concentration after the DUT is blocked. The hazards of this failure and the expected further research are mentioned simply. Highlights: The analysis of the role of HSB vs. LSB (the classical one) is original. The further electric field concentration after LSB SC was found in TCAD simulation. DUTs, which failed, were decapsulated from the side of the drain to allow for an emission microscope (EMMI) investigation.